Diferentes lâminas de irrigação no cultivo da bananeira Prata Anã em Missão Velha - CE - Lopes, Cleomar Bizonhin (2018)
Given the economic importance of banana cultivation in Brazil and in the Brazilian Northeast, the high water requirement of this crop, the increasing competition for water use, economic pressures on producers and the environmental impacts caused by the use of irrigation, the main purpose of this research is to study the effects of the reduction of irrigation on the development and productivity of banana plantation. The experiment was carried out at the commercial farm of Barriers Site Fruticulture Ltda, located in the municipality of Mission Valhi - CE. The experimental design was a randomized block, with five treatments with different irrigation plates based on fractions of crop evapotranspiration (34, 56, 78, 100 and 122% of ETc), and five replications. The vegetative development of the crop, the productive variables and the cost of water and energy in the total gross income were evaluated. The results evince that the treatment corresponding to 122% of ETc, under the conditions in which the research was performed, provided higher productivity than the other studied treatments, however the treatment with 78% of ETc presented higher water productivity, therefore reducing the irrigation plate to 78% of ETc is a viable option for water scarcity situations in established banana plantations. Irrigation treatments did not influence on fruit quality at post harvest, however, they affected fruit quality at harvest, but the irrigation plate at 122% of ETc had better results in obtaining higher percentages of fruits of first and second quality, when compared to other treatments. The water and electricity costs in relation to the gross income in the 34, 56, 78, 100 and 122% ETc treatments were, respectively, 8.25%, 8.42%, 5.14%, 5.09 % and 4.98%.